PS-036 Improving pharmacological treatment: Real time safety audits. (14th February 2016) - Canadell, L; Olona, M; Sirgo, G; Gilabert, MC; López, PA; Martín, M; De dios, A; Canela, M; Bodí, M
Abstract : Background: Patients admitted to intensive care units (ICU) are characterised by their need for a more advanced level of care and a higher risk of patient safety related incidents. Errors in pharmacological treatments may occur due to an unintended act or by omission. Errors of omission are more insidious and more difficult to identify. Purpose: The two aims of this study were first to present a checklist designed to improve the pharmacotherapeutic care process and the second was to present the results obtained with this tool in our ICU. Material and methods: This was a prospective study conducted over a period of 1 year in one adult ICU (14 beds). The checklist consisted of 37 safety measures, 10 focused on treatment. It was performed 3 days per week, with randomisation of 50% of the safety measures and 50% of the ICU patients on each day of the analysis. Although the measures included in the checklist are routinely carried out by healthcare professionals during the ICU daily round, the purpose of the safety audit was to verify that they had actually been carried out. If this was not the case (error of omission), the prompter reminded the healthcare professionals that they should carry them out. Results: Pharmacological treatment measures (PT) were evaluated on 476 occasions: allergies, prescription, indication, dosage, verbal orders, prophylaxis of thromboembolic disease, gastrointestinal haemorrhage, glycaemic control and antibiotic adequacy. Nutrition (N) was evaluated on 341 occasions. Globally, measures correctly performed on the ICU daily round were 96.85% for PT and 64.81% for N. Multivariate analyses did not demonstrate significant changes in the pharmacological care process when variables were analysed quarterly, except for improving lack of verbal prescription (26% to 2.2%, p < 0.05) and improving management of nutrition (58.33% to 72.62%, p < 0.05). Furthermore, the audit was useful to detect errors of omission and to correct them promptly in 8.3% of cases. Conclusion: Real time safety audits in medication help to verify the adequacy of pharmacological orders and can increase safety awareness. The tool has been useful to improve nutrition management. No conflict of interest.